External apical root resorption in orthodontically treated Class II malocclusions with 2-phase protocol (A 10-year Experience) - Omar Fawzi Chawshli (Erbil Dental Journal)
Background and objectives: External apical root resorption is one of the proposed sequels of fixed orthodontic appliances used for the treatment of different types of malocclusions specially class II. Many factors may be involved in the etiology and severity of such resorption. This study is conducted to explore the prevalence of root resorption and specify the most possible causative factors during orthodontic treatment.